Allelopathic effect of invasive plants (Eriochloa villosa, Asclepias syriaca, Fallopia x bohemica, Solidago gigantea) on seed germination - Szilágyi, Arnold; Radócz, László; Tóth, Tamás (Acta Agraria Debreceniensis, 2018)
The aim of this study was to determine the allelopathic potential of invasive species woolly cupgrass (Eriochloa villosa), common milkweed (Asclepias syriaca), bohemian knotweed (Fallopia x bohemica), and giant goldenrod (Solidago gigantea Ait.) on germination crop (Lepidium sativum L.). Experiments were conducted under laboratory conditions to determine effect of water extracts in petri dish bioassay. Water extracts from fresh biomass (leaves and stem) of invasive weeds in concentrations of 4 and 8 g/100 ml were investigated. All invasive plants showed allelopathic effect on germination. In giant goldenrod stem water extract experiment, allelopathic effect was less pronounced.The cress germination was greatly suppressed with the woolly cupgrass, common milkweed and the giant goldenrod. The experiment showed that the seed germination depended on the concentrations and the plant material used (leaves and stem).